An iridium(III) complex-based luminogenic probe for high-throughput screening of hydrogen sulfide donors in living cells - Ke-Jia Wu; Wen Sun; Jian-Min Sun; Chang Lu; Ning Sun; Chung‐Hang Leung; Yan Li; Chun Wu (Communications Chemistry)
Abstract The scarcity of suitable high-throughput screening technology for hydrogen sulfide (H2S) donors has hampered the discovery of H2S donors. In this study, a long-lived cyclometalated iridium complex was rationally designed as a mitochondria-targeted H2S probe to monitor the real-time dynamic change of H2S. By using the time-resolved emission spectroscopy (TRES) technique, an anti-interference high-throughput screening system was developed to monitor H2S in living cells with decreased false negative results. As a proof-of-concept, three natural products were identified as potential H2S donors from a natural product library using the developed TRES probe. Notably, the discovery of allicin and diallyl trisulfide demonstrated the feasibility of this screening platform, while garlic-derived allyl methyl sulfide was explored as a H2S donor candidate. The results were further validated by a commercial assay. We anticipate this high-throughput platform could facilitate the discovery of H2S donors by discriminating the endogenous interfering fluorescence from biological systems.